Meat yield and meat quality characteristics of backcrossed Sonali chicken compared to Aseel♂ × Sonali♀ and Hilly♂ × Sonali♀ crossbreds - MS Ali; M Habib; MSA Bhuiyan; MAK Azad; MA Hashem; MH Ali (Meat Research, 2022)
The experiment was conducted to assess the meat yield and meat quality characteristics of backcrossed Sonali chicken compared to Aseel♂ × Sonali♀ and Hilly♂ × Sonali♀ crossbreds during 0, 15 and 30 days of storage. Therefore, 6 male birds from each of 4 genotype i.e. RIR♂ × Sonali♀, Fayoumi♂ × Sonali♀, Aseel♂ × Sonali♀ and Hilly♂ × Sonali♀ around 1.2 kg of body weight were slaughtered, eviscerated and dissected to compare meat yield and meat quality characteristics during 0, 15 and 30 days of storage period. The results showed that there were no significant differences among the genotypes on meat yield, proximate, physio-chemical and biochemical characteristics of backcrossed Sonali chicken compared to Aseel♂ × Sonali♀ and Hilly♂ × Sonali♀ crossbreds. Drip loss, cooking loss, pH and CP% decreased, while DM%, EE%, ash%, peroxide value, free fatty acid value, thiobarbituric acid value increased with the increasing of storage time. The present study reveals that backcrossing had no demerits on meat quality and yield characteristics.